Quality of life and promotion of social well-being through biophilia in urban planning (Interdisciplinary Studies Journal, 2024)
The lack of infrastructure in urban areas is evident and has a significant impact on reducing the quality of life of urban residents, resulting in a range of widely perceived problems such as environmental pollution, visual pollution, and noise pollution. The present text aims to reflect on the concept of biophilia, highlighting its relevance in the current context of cities and outlining how it can play a crucial role in urban quality of life through green spaces, reducing air pollution, noise pollution, and promoting physical and emotional well-being. Through a qualitative descriptive approach, the research utilizes bibliographic review and documentary research. The results show that urban planning should promote the healthy growth and development of cities, ensuring social well-being as a fundamental right for all who live in these environments. It is noted that the relationship between exposure to green spaces, physical and mental health, and the need to offer moments of leisure, social integration, and physical activity is crucial to addressing the challenges of population density in large cities and can significantly contribute to the quality of life of the urban population.
Keywords: Urban Planning; Well-being; Green Spaces; Biophilia